Homology between the glycoproteins of vesicular stomatitis virus and rabies virus. - Rose, J K (1982)
We compared the predicted amino acid sequences of the vesicular stomatitis virus and rabies virus glycoproteins by using a computer program which provides an optimal alignment and a statistical significance for the match. Highly significant homology between these two proteins was detected, including identical positioning of one glycosylation site. A significant homology between the predicted amino acid sequences of vesicular stomatitis virus and influenza virus matrix proteins was also found.